High school students' learning motivation in mathematics learning in the independent curriculum - Ovilia Nur Wida; Darsono Darsono; Dian Devita Yohanie (Universitas Muhammadiyah Lampung, 2026)
Learning motivation is a crucial factor in mathematics learning in high school, particularly in the implementation of the Independent Curriculum. However, it still shows variation and tends to decline during the transition period. This study aims to describe students' learning motivation and analyze the intrinsic and extrinsic factors that influence it in mathematics learning under the Independent Curriculum. The study used a descriptive qualitative approach and was conducted at SMA Negeri 6 Kediri City. The research subjects consisted of six tenth-grade students selected through purposive sampling based on differences in academic ability levels. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that students' learning motivation was categorized as high, medium, and low, influenced by intrinsic and extrinsic motivational factors. The main findings indicate that the most dominant factors influencing learning motivation were interesting learning activities and active student involvement, while the lack of learning variation was the main cause of low motivation in some students.